Facile Conversion of α‐Acyloxy Amides into 3‐Hydroxy‐lactams. Issue 25 (25th June 2018) - Koszelewski, Dominik; Trzepizur, Damian; Zaorska, Ewelina; Madej, Arleta; Brodzka, Anna; Paprocki, Daniel; Borys, Filip; Wilk, Monika; Ostaszewski, Ryszard
Abstract : The new synthetic route to α‐acyloxy amides based on Passerini multicomponent reaction followed by transformation into the corresponding five‐, six‐, and seven‐membered 3‐hydroxy‐lactams has been proposed. The influence of the reaction conditions, which includes substrate structure on the reaction course that led to desired lactams, was studied. The use of various oxo components in the Passerini multicomponent reaction (P‐MCR) has been evaluated. The first example of a semicyclic O, O ‐acetal employed as an aldehyde equivalent in the P‐MCR has been reported. Finally, the established protocol was successfully applied for the enantioselective synthesis of 3‐hydroxy‐lactams, which play a crucial role in the synthesis of the number of bioactive compounds. Abstract : A synthetic route to α‐acyloxy amides based on P‐MCR followed by transformation into the corresponding 3‐hydroxy‐lactams has been developed. Established protocol was successfully applied in the synthesis of various five‐, six‐, and seven‐membered rings of 3‐hydroxy‐lactams, which play a crucial role in the synthesis of the number of bioactive compounds.